The Topography of The Female Self in Indian Therapeutic Cults - Carrin, Marine (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2011)
Anthropologists have stressed the relationship between symptoms of distress, ritual action and unwanted possession. The article stresses the importance of language and performance in two therapeutic cults in India. The crucial issue here involves showing how ritual becomes a means for either representing or manipulating special mental states. We see how individuals may use possession as a strategy to frame a reformulation of the self. Healing thus involves self-awareness.